Add a comment … how fitspiration and body positive captions attached to social media images influence the mood and body esteem of young female Instagram users. (June 2020) - Davies, Bryony; Turner, Mark; Udell, Julie
Highlights: Identical images from Instagram were viewed with different image captions. Fitspiration-style image captions increased negative mood in observers. Fitspiration-style and neutral image captions were associated with poorer weight esteem. Image captions advocating body positivity were associated with better weight esteem. Caption type had no effect on sexual or physical conditioning esteem. Abstract: Social media content can negatively influence body esteem in young women by reinforcing beliefs that to be considered attractive, people must look a certain way. The current study examines how text associated with attractive social media images impacts on female users' mood and feelings about their own body. Female participants ( N = 109) aged between 18 and 25 years were randomly allocated to one of three conditions in which they viewed the same fitspiration-style images from Instagram. However, the captions associated with each image were experimentally manipulated to reflect either a fitspiration, body positive, or neutral theme. Images associated with fitspiration captions encouraging observers to improve their personal fitness led to increased negative mood. When body-positive captions encouraging the self-acceptance of appearance or highlighting the unrealistic nature of social media content were viewed with the same images, no increase in negative affect was observed, and participants reported greater body esteem post exposure. The findings provide partial support for the idea that body positive comments accompanying images on Instagram may have some protective value for female body esteem. Captions may play an important part in observers' reactions to social media images, beyond the influence of the images alone.